A COMPARISON OF CLASSICAL AND MODERN ISLAMIC PHILOSOPHY: FROM AL-KINDI TO SEYYED HOSSEIN NASR - Adit Mohammad Aziz (Adisam Publisher, 2025)
A comparison between classical and modern Islamic philosophy can be seen through the works and thoughts of two great intellectuals: Al-Kindi and Seyyed Hossein Nasr. Al-Kindi, as an icon of classical Islamic philosophy, is famous for his efforts to incorporate Greek philosophical thought into Islamic teachings, showing openness to knowledge from diverse civilisations. On the other hand, Seyyed Hossein Nasr, a contemporary thinker, rejected the influence of modern secularism and materialism, emphasising the importance of maintaining the integrity of Islam's spiritual tradition. Although their approaches differ, both share a dedication to the propagation and maintenance of Islamic intellectual and spiritual values. This analysis illustrates how Islamic philosophy evolves in the face of the challenges of each age, remaining relevant and providing a rich perspective in understanding and dealing with the dynamics of the modern world.